PENEGAKAN HUKUM OLEH KEPOLISIAN RESOR PADANG LAWAS TERHADAP PEMERASAN YANG DILAKUKAN PREMAN - Irma Laras Wati; Davit Rahmadan; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Incidents of extortion on the road still frequently occur, causing distress tothe community that traverses the Trans-Sumatra Highway in Padang LawasRegency. In this regard, the participation of the Padang Lawas District Police isgreatly needed to address extortion crimes in Padang Lawas Regency, ensuringthat the passing community feels safe and implementing preventive measures toprevent the recurrence of extortion crimes in Padang Lawas Regency.This type of research can be classified into the type of sociologicalresearch which is carried out by direct research at the place being studied toprovide a complete and clear picture of the problem under study. This researchwas conducted at the Padang Lawas District Police, while the population and thesample were parties related to the problems studied in this study, the data sourcesused were; primary data, secondary data, and tertiary data, data collectiontechniques in this study by interviews, questionnaires, and literature study.From the results of this research there are three main things that can beconcluded. Firstly, law enforcement by the Padang Lawas District Police againstextortion committed by thugs has not been carried out properly and effectively.Secondly, the obstacles faced by the Padang Lawas District Police in enforcingthe law against extortion committed by thugs are due to factors such asinadequate infrastructure or facilities to support law enforcement, communityfactors, and a shortage of personnel in the Padang Lawas District Police. Third,the efforts made by the Padang Lawas District Police in overcoming obstacles tolaw enforcement extortion by thugs are utilizing personnel by carrying out goodcooperation between personnel at the Padang Lawas District Police, coordinatingwith government institutions and the community, and conducting legaloutreach/socialization to the public. The author's suggestion, First, is that thePadang Lawas District Police be able to carry out more solid cooperation andcoordination with government institutions and the community. Secondly, thePadang Lawas District Police should maximize patrols and reporting systems.Thirdly, the Padang Lawas District Police and the Padang Lawas Regency LocalGovernment are expected to develop programs to address the underlying causesof extortion carried out by thugs.Keywords: Law Enforcement - Extortion - Committed by Thugs